Enhancing Compressed Earth Blocks with Eggshell and Lime: Effects on Mechanical and Physical Properties (London Journal of Engineering Research, 2024)
This study examined the engineering, microstructural, and elemental properties of compressed earth blocks (CEBs) stabilised with eggshells and lime. Experiments were conducted on 140 × 100 x 100 mm earth blocks stabilised with 10% constant lime and 0, 0.25, 0.5, 0.75, 1% eggshell contents. CEBs were tested for density, water absorption, tensile strength, compressive strength, erosion, chemical composition, and microstructural on 7, 14, 21, and 28 curing days. At 28 days of curing, the 1% eggshell and 10% lime-stabilised compressed earth blocks recorded compressive and tensile strengths of 1.33 and 0.173 N/mm2, respectively compared with the unstabilised compressed earth blocks’ strength of 1.01 and 0.14 N/mm2. The eggshell and lime-stabilised compressed earth blocks also exhibited reduced water absorption of 3.32% compared to unstabilised blocks of 4.62%. SEM and EDS analyses further confirmed the microstructural properties and contribution of key elements like calcium to enhanced mechanical properties. The study concludes that the presence of eggshells and lime in the earth matrix enhanced the properties of the compressed earth blocks.  It is recommended that block manufacturers enhance the properties of the compressed earth blocks should with 1% eggshell and 10% lime.
Keywords: pirate attacks; risk analysis; K-means clustering; Autoencoder; EWM-TOPSIS; Compressive Strength; tensile strength; mechanical properties; compressed earth blocks (CEBs); eggshell waste; lime